Abu Bakr As-Siddeeq : His Life & Time - Ali M. Sallabi, Dr.; Translated by Nasiruddeen Al-Khattab (Riyadh International Islamic Publishing House, 2012)
Islamic Empire; history, 622-661.
Include Glossary and Index
Keywords: Biography